Symptomatic Congenital Cytomegalovirus Infection in Children of Seropositive Women - Mack, Ines; Burckhardt, Marie-Anne; Heininger, Ulrich; Prüfer, Friederike; Schulzke, Sven; Wellmann, Sven (Frontiers in Pediatrics, 2017)
Cytomegalovirus (CMV) is the most frequent congenital virus infection worldwide. The risk of congenital CMV (cCMV) transmission is highest in seronegative women who acquire primary CMV infection during pregnancy. A growing body of evidence indicates that secondary CMV infections in pregnant women with preconceptual immunity (either through reactivation of latent virus or re-infection with a new strain of CMV) contribute to a much greater proportion of symptomatic cCMV than was previously thought. Here we describe a case of symptomatic cCMV infection in a woman with proven immunity prior to pregnancy. Diagnosis was confirmed by CMV-PCR from amniotic fluid and fetal MR imaging. The newborn presented with typical cCMV symptoms including jaundice, hepatosplenomegaly, cholestasis, petechiae, microcephaly and sensorineural hearing loss, the most common neurologic sequelae. CMV was detected in infant blood and urine by PCR, and intravenous ganciclovir was initiated and continued orally for 6 weeks totally. Apart from persisting right-sided deafness, the child exhibited normal neurological development up through the last follow-up at 4.5 years. To date, the most effective strategy to prevent vertical CMV transmission is hygiene counseling for women of childbearing age, which, in our case, and in concordance with recent literature, applies to seronegative, as well as seropositive, women. Once an expecting mother shows seroconversion or signs of an active CMV infection, there are no established procedures to reduce the risk of transmission, or therapeutic options for the fetus with signs of infection. After birth, symptomatic infants can be treated with ganciclovir to inhibit viral replication and improve hearing ability and neurodevelopmental outcome. A comprehensive review of the literature, including our case study, reveals the most current and significant diagnostic and treatment options available. In conclusion, the triad of maternal hygiene counseling, postnatal hearing screening of all newborns, followed by CMV-PCR in symptomatic infants, and antiviral therapy of infants with symptomatic cCMV, provides an outline of best practice to reduce the burden of CMV transmission sequelae.